A simple method to control the formation of cerium phosphate architectures. Issue 44 (15th October 2015) - Pusztai, P.; Tóth-Szeles, E.; Horváth, D.; Tóth, Á.; Kukovecz, Á.; Kónya, Z.
Abstract : Two development pathways are identified by which the formation of architecturally different cerium phosphate spherulites can be triggered. The selection between these mechanisms can readily be achieved by the reverse addition of precursors. Structural differences significantly alter the photoluminescence properties of the spherulites. Abstract : Growth of cerium phosphate microstructures was examined under mild conditions using a flow reaction system. Two entirely different development pathways were identified by which the formation of architecturally different cerium phosphate spherulites could be triggered. The selection between these mechanisms could readily be achieved by the reverse addition of precursors. Structural differences were examined by using scanning electron microscopy, high-resolution transmission electron microscopy, X-ray diffractometry and nitrogen sorption measurement. The precipitate flow profiles were examined comprehensively and taken into consideration to interpret the spherulite formation process. The presumed formation mechanisms were approved by time monitored synthesis and HRTEM investigation. Terbium-doped counterparts of the pristine spherulites were used to assess the structure-related photoluminescence properties. Regardless of the identical crystal phase and chemical composition, a 30–35% difference in photoluminescence intensity was found between the two types of spherulites, suggesting strong architecture-dependent physical properties.